2020
DOI: 10.1371/journal.pone.0243262
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality risk assessment: An international multi-center study

Abstract: Timely identification of COVID-19 patients at high risk of mortality can significantly improve patient management and resource allocation within hospitals. This study seeks to develop and validate a data-driven personalized mortality risk calculator for hospitalized COVID-19 patients. De-identified data was obtained for 3,927 COVID-19 positive patients from six independent centers, comprising 33 different hospitals. Demographic, clinical, and laboratory variables were collected at hospital admission. The COVID… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
151
1
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(185 citation statements)
references
References 27 publications
14
151
1
19
Order By: Relevance
“…As reported, the most frequently reported predictors were age, clinical status such as temperature, imaging results from chest radiography, and lymphocyte count. Recently, a study including 3927 patients from 33 hospitals developed the COVID-19 Mortality Risk (CMR) tool using the XGBoost algorithm 27 . This score is based on age, blood urea nitrogen, CRP, creatinine, glucose, AST, and platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the most frequently reported predictors were age, clinical status such as temperature, imaging results from chest radiography, and lymphocyte count. Recently, a study including 3927 patients from 33 hospitals developed the COVID-19 Mortality Risk (CMR) tool using the XGBoost algorithm 27 . This score is based on age, blood urea nitrogen, CRP, creatinine, glucose, AST, and platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…1 Generally, COVID-19 is more severe in people aged >60 years or those with underlying diseases. 2,3 Research on COVID-19 has been conducted from various perspectives, such as infection cases, 4,5 clinical characteristics, [6][7][8] and preventive measures. 9 In addition, several studies have confirmed that COVID-19 is more severe in older people and those with underlying diseases, such as lung or heart disease, diabetes, and immunological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that levels of CRP above 130 mg/l may be associated with increased mortality [ 3 ]. Albumin levels are significantly lower in severe COVID-19, but the change in albumin levels does not parallel the severity of hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, combined analysis of liver enzymes and platelet counts has provided important information on new biomarkers used to determine the severity of infectious and neoplastic diseases [ 1 , 2 ]. Moreover, thrombocytopenia and lymphopenia in severe COVID-19 patients are associated with an increased risk and even coagulopathy has poor prognosis [ 3 , 4 ]. Elevated aspartate aminotransferase lymphocyte ratio index (ALRI) levels prior to treatment seem to be indicators of poor prognosis in colorectal cancer [ 5 ].…”
mentioning
confidence: 99%